Effect of interleukin 2 on killer cell inhibitory receptors in patients with rheumatoid arthritis. Issue 2 (1st February 2001) - Kogure, T; Niizawa, A; Hai, L X; Fujinaga, H; Shimada, Y; Ochiai, H; Terasawa, K
Abstract : OBJECTIVE: The genes for killer cell inhibitory receptors (KIRs) have been cloned and their functions and responses to other molecules, including cytokines, have been partially clarified. However, the expression of KIRs has not been analysed in patients with autoimmune diseases, such as rheumatoid arthritis (RA), who are highly susceptible to microbial infection. Therefore, KIR expression on lymphocytes in patients with RA, and the regulation of KIR expression by interleukin 2 (IL2) in RA was investigated. METHODS: CD158a/b expression on peripheral blood mononuclear cells (PBMC) obtained from 25 patients with RA and 14 healthy subjects was analysed by flow cytometry. Additionally, PBMC from the two groups of subjects were cultured in RPMI 1640 medium with or without IL2 for 48 hours, and then their CD158a/b expression was analysed. RESULTS: The rate of CD158a expression on the CD8+ cells was lower in patients with RA than in healthy subjects, though there was no significant difference in the CD158a/b expression on the CD16+ cells between the two groups. The upregulation of CD16+CD158a/b+ cells in response to IL2 was significantly reduced in patients with RA compared with healthy subjects. CONCLUSION: The reduced induction of KIR expression in response to IL2 may provide insight into the reason for the high susceptibility of patients with RA to microbial infection.